The COX-2 Inhibitor Celecoxib Sensitizes Nasopharyngeal Carcinoma Cells to Ferroptosis - Li, Dawei; Guo, Shuang; Wang, Kunrong; Liu, Zhaoqi; Yu, Taixin; Zhang, Yingqiu (Current Cancer Drug Targets, 2025)
<span class=
Keywords: CHAC1